Vamos pertencer e nos encontrar juntos : narrativas compartilhadas, afetos e subjetivação no Projeto Guardei no Armário - Pereira, Pedro Augusto Elias Cardoso (2022)
The objective of this master's research is to understand how the "coming out of the closet" is configured in the testimonies of black gay subjects / bichas pretas in Project Guardei no Armário, created by Samuel Gomes. From an intersectional methodological perspective based on Patricia Hill Collins (2017; 2019), bell hooks (2019), Grada Kilomba (2019) and Lélia Gonzalez (1984), in dialogue with the “method of the scene” or “of equality” proposed by Jacques Rancière (2021), I seek a methodological path that opposes to binarism and hierarchies, seeking to understand, rather than explain, according to an equality between intelligences. Through the analysis of some testimonies gathered in the project, considered as writing/escrevivência and elaboration, both individual and collective, as processes of subjectivation, I propose a look at this so-called “coming out of the closet” as a subjective and political, intersectional process, going beyond the more usual definitions of coming out of the closet only as a moment of announcement, or of a revealed secret. Coming out of the closet, from Guardei no Armário, appears as a process permeated by an LGBT+ collectivity and ancestry.